Alkynes as Electrophilic or Nucleophilic Allylmetal Precursors in Transition‐Metal Catalysis. Issue 38 (10th August 2017) - Haydl, Alexander M.; Breit, Bernhard; Liang, Tao; Krische, Michael J.
Abstract: Diverse late transition metal catalysts convert terminal or internal alkynes into transient allylmetal species that display electrophilic or nucleophilic properties. Whereas classical methods for the generation of allylmetal species often form stoichiometric by‐products, the recent use of alkynes as allylmetal precursors enables completely atom‐efficient catalytic processes to be carried out, including enantioselective transformations. Abstract : The best of both worlds : Diverse late transition metal catalysts can convert terminal or internal alkynes into transient allylmetal species that display electrophilic or nucleophilic properties. The use of alkynes as allylmetal precursors enables completely atom‐efficient catalytic processes to be carried out, including enantioselective transformations.